Elucidating mesomorphic and electrical properties of conjugated acetylide-imine as electrochemically deposited electron transporting materials in organic conductive film - Khairul, Wan Mohd; Foong, Y.D.; Sarih, Norazilawati Muhamad; Lee, Oon Jew; Lim, Soon Kit Julian; Daud, Adibah Izzati; Rahamathullah, Rafizah (Akademi Sains Malaysia, 2018)
A new class of liquid crystalline acetylide-imine system was successfully synthesized, characterized and deposited on indium tin oxide (ITO) coated substrate via electrochemical deposition method for potential organic film application. The relationship between liquid crystal molecular structure, phase transition temperature and electrical performance was evaluated. The mesomorphic properties were identified via polarized optic microscopy (POM) which displayed fan-shaped texture of smectic A phase and their corresponding transition enthalpies are in concurrence with DSC and TGA studies. The findings from the conductivity analysis revealed that the fabricated film exhibits good electrical performance where it displayed linear current-voltage relationship of I-V curve. Therefore, this proposed type of molecular framework has given an ideal indication to act as transporting material for application in optoelectronic devices.